Intermittent Bi-Daily Sub-cutaneous Teriparatide Administration in Children With Hypoparathyroidism: A Single-Center Experience - Bernardor, Julie; Flammier, Sacha; Cabet, Sara; Lemoine, Sandrine; Chapurlat, Roland; Molin, Arnaud; Bertholet-Thomas, Aurélia; Bacchetta, Justine (Frontiers in Pediatrics, 2021)
Introduction: The use of teriparatide has been reported in children with hypoparathyroidism as an investigational physiologic replacement therapy. Methods: We aimed to retrospectively report our pediatric experience of bi-daily sub-cutaneous teriparatide. Results are presented as median (25th−75th quartile). As part of the routine follow-up of these patients with hypoparathyroidism, total calcium at H0 (i.e., just before injection) and H4 (i.e., 4 h after teriparatide injection) and other biomarker parameters were regularly assessed. Results: At a median age of 10.7 (8.1–12.6) years, an estimated glomerular filtration rate (eGFR) of 110 (95–118) mL/min/1.73 m2, calcium levels of 1.87 (1.81–1.96) mmol/L and an age-standardized phosphate of 3.8 (2.5–4.9) SDS, teriparatide therapy was introduced in 10 patients at the dose of 1.1 (0.7–1.5) μg/kg/day (20 μg twice daily), with further adjustment depending on calcium levels. Six patients already displayed nephrocalcinosis. Severe side effects were reported in one child: two episodes of symptomatic hypocalcemia and one of iatrogenic hypercalcemia; one teenager displayed dysgueusia. Calcium levels at H0 did not significantly increase whilst calcium at H4 and phosphate levels significantly increased and decreased, respectively. After 12 months, eGFR, calcium and age-standardized phosphate levels were 108 (90–122) mL/min/1.73 m2, 2.36 (2.23–2.48) mmol/L, 0.5 (−0.1 to 1.5), and 68 (63–74) nmol/L, respectively, with a significant decrease in phosphate levels (p = 0.01). Urinary calcium and calcium/creatinine ratio remained stable; no nephrolithiasis was observed but two moderate nephrocalcinosis appeared. Conclusion: Intermittent teriparatide therapy significantly improves calcium and phosphate control, without increasing calciuria. It appears to be safe and well-tolerated in children.